KINERJA PUSTAKAWAN PADA LAYANAN DEPOSIT DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI KALIMANTAN BARAT - Adilla, Indriyati; Hanum, Atiqa Nur Latifa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe librarian is one of the activator elements and organization of service activities, without the librarian who organize and provide services, the library will not have services. The problem raised by the writer is â€œLibrarian Performance in the Deposit Service of the Library and Archives Service of West Kalimantan Provinceâ€. The purpose of this research is to determine the performance of the librarian on deposit services, the factors that influence and the effort made to improve the performance of the librarian. The type of research that will be used is descriptive qualitative research. Data collection is by using observation and interviews, and documentation technique. A technique of data analysis is carried out with data reduction, data model and with conclusion. The result of study showed that a performance of librarian is good. It cause the given job to librarians is finished by responsibility and on time. A factor of influence performance are self factors and work environment factors. A conclusion to increase a performance of librarian is following technical guidance, workshop, traning for adding experience and science library.Â Keywords: Deposit Service, Performance Librarian, Province Library, West Kalimantan